What philosophers should know about truth - Stoutland, Frederick (Berlin studies in knowledge research ;, 2019)
"Fred Stoutland was a major figure in the philosophy of action and the philosophy of language. This collection brings together essays on truth, language, action and mind and thus provides an important summary of many key themes in Stoutland's own work, as well as offering valuable perspectives on key issues in contemporary philosophy." --